2019
DOI: 10.3319/tao.2019.02.15.01
|View full text |Cite
|
Sign up to set email alerts
|

A deep-towed magnetic survey in the southern Okinawa Trough: Implications for hydrothermal system detection

Abstract: The Okinawa Trough (OT) is widely recognized as an area with extensive volcanism and hydrothermal activity. However, finding new hydrothermal vent sites in this region remains a technical challenge due to their small sizes. A deep-towed magnetic survey can acquire short-wavelength signals, which can provide useful information on the shallow subsurface structures of hydrothermal systems. In 2017, a deep-towed magnetic survey was conducted in selected area of the southern OT. After data processing and removing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…In our study region, the heat flow in the south region may be a consequence of asymmetric spreading of the back-arc. Previous studies (Oshida et al, 1992;Doo et al, 2019) showed an asymmetric magnetic anomaly distribution in our study region -the magnetic anomaly in the south is higher than that in the north. However, because we do not have a high resolution lithosphere depth in the study region, we do not have sufficient evidence to support the asymmetric spreading hypothesis.…”
Section: High Heat Flowcontrasting
confidence: 42%
“…In our study region, the heat flow in the south region may be a consequence of asymmetric spreading of the back-arc. Previous studies (Oshida et al, 1992;Doo et al, 2019) showed an asymmetric magnetic anomaly distribution in our study region -the magnetic anomaly in the south is higher than that in the north. However, because we do not have a high resolution lithosphere depth in the study region, we do not have sufficient evidence to support the asymmetric spreading hypothesis.…”
Section: High Heat Flowcontrasting
confidence: 42%
“…An apparent acoustically transparent zone was imaged in the shallow sediments of the two sites (Hsu, 2017), suggesting a very active fluid/gas circulation system (Hsu, 2017; Hsu et al., 2019). In addition, the low magnetic anomalous behavior of the two sites also suggests a high hydrothermal potential due to hydrothermal alteration and metasomatism (Doo et al., 2019; Huang et al., 2019).…”
Section: Geological Backgroundmentioning
confidence: 99%